Penyelenggaraan Pemerintahan Nagari di Bawah Bayang Negara (Studi Kasus Pemerintahan Nagari Balah Aie) - Rhevi Aliza; Tengku Rika Valentina; Roni Ekha Putera (Jurnal Ilmu Hukum, Humaniora dan Politik, 2024)
Village Law No. 4 2016 does not guarantee the granting of full authority to the nagari government. The administration of nagari government is dominated by the state. Where all forms of programs have been regulated by the government above them through the regulations and policies they issue. The emergence of a number of policies issued by the government through its ministries means that government administration cannot move and must implement them. For example, Presidential Regulation Number 104 of 2021 concerning details of the APBN for the 2022 fiscal year in article 5 paragraph (4) regulates the use of Village Funds for 2022, one of which is through a social protection program in the form of Direct Cash Assistance (BLT) for villages of at least 40% of total revenue. village funds and 20% for food security and improvement programs and 8% for preventing and handling Covid-19. As well as Regulation of the Minister of Village PDTT RI Number 7 of 2021 concerning Priority Use of Village Funds in 2022, and Regulation of the Minister of Finance of the Republic of Indonesia Number 190/PMK.07/2021 concerning Management of Village Funds. Based on these regulations, it is clear that the administration of the Nagari government must follow this, including the administration of the Nagari Balah Aie government which is also inseparable from the policy commands that have been blinded by the government above.